Differentiated TGT on Mathematics Learning Outcomes and Problem-Solving Skills of Elementary Students - Laelu Rafika; Suriswo Suriswo; Dewi Apriani (FKIP - Universitas Riau, 2026)
Mathematics learning in elementary school plays an essential role in developing students’ logical reasoning and problem-solving skills; however, many students still experience difficulties in solving non-routine mathematical problems, particularly in heterogeneous classrooms. This study examined the effect of a differentiated Teams Games Tournament (TGT) cooperative learning model on mathematics achievement and problem-solving skills of elementary students. A quantitative quasi-experimental method with a nonequivalent control group design was employed. The participants were fifth-grade students of SD Negeri 01 Kebondalem, Pemalang Regency, Indonesia, divided into an experimental group receiving differentiated TGT instruction and a control group taught using conventional methods. Data were collected through pretests and posttests measuring mathematics achievement and problem-solving skills based on Polya’s stages. The results showed that the experimental group achieved higher learning outcomes and demonstrated better problem-solving skills than the control group. These findings indicate that integrating differentiation principles into the TGT model effectively improves mathematics achievement and problem-solving skills in elementary education.